INCREASING THE EFFICIENCY OF EDUCATION TEACHING THROUGH THE USE OF DIGITAL EDUCATIONAL PLATFORMS (Universal International Scientific Journal, 2026)
This article discusses the issues of increasing the effectiveness of teaching education through the use of digital educational platforms. It analyzes the possibilities of organizing the educational process using modern information and communication technologies, increasing students' interest in learning, and enriching the lesson process through interactive methods. It also considers the advantages of digital platforms in the educational process, their role in developing students' independent thinking, creative approach, and spiritual and moral education. According to the results of the study, the effective use of digital educational tools serves to improve the quality of teaching education and ensure the effectiveness of the educational process.
Keywords: digital education, digital platforms, educational science, innovative technologies, information and communication technologies, interactive education, educational effectiveness, e-learning.